Complex Regulation of the Pericellular Proteolytic Microenvironment during Tumor Progression and Wound Repair: Functional Interactions between the Serine Protease and Matrix Metalloproteinase Cascades - Cynthia E. Wilkins-Port; Stephen P. Higgins; Craig E. Higgins; Issey Kobori-Hotchkiss; Paul J. Higgins (Biochemistry Research International, 2012)
Spatial and temporal regulation of the pericellular proteolytic environment by local growth factors, such as EGF and TGF-β, initiates a wide repertoire of cellular responses coupled to a plasmin/matrix metalloproteinase (MMP) dependent stromal-remodeling axis. Cell motility and invasion, tumor metastasis, wound healing, and organ fibrosis, for example, represent diverse events controlled by expression of a subset of genes that encode various classes of tissue remodeling proteins. These include members of the serine protease and MMP families that functionally constitute a complex system of interacting protease cascades and titrated by their respective inhibitors. Several structural components of the extracellular matrix are upregulated by TGF-β as are matrix-active proteases (e.g., urokinase (uPA), plasmin, MMP-1, -3, -9, -10, -11, -13, -14). Stringent controls on serine protease/MMP expression and their topographic activity are essential for maintaining tissue homeostasis. Targeting individual elements in this highly interactive network may lead to novel therapeutic approaches for the treatment of cancer, fibrotic diseases, and chronic wounds.